Faustino Miranda (1905-1964). Nuevos datos relacionados con su formación botánica en España y con su contribución a la Ficología marina. - Dosil, F.J.; Cremades, J.; Fraga, X.A. (Botanica Complutensis, 2001)
DOSIL MANCILLA, F. J., CREMADES UGARTE, J. & FRAGA VÁZQUEZ, X. A. 2001. Faustino Miranda (1905-1964). New data about his botanical formation in Spain and his marine Phycology contribution. Bot. Complutensis 25: 191-205. Aspects bad-known of Faustino Miranda's phycological activity are developed in this paper. We analyse his formation period in France, where he could work with prominent phycologist, and the activity that Miranda developed in the Station of marine biology of Marin (Pontevedra), where he teached first phycologist course in Spain, and where he could investigate about the Galician marine flore. These dates remark his excelent preparation as phycology and his key paper in the spanish phycologist institucionalitation. The Civil War (1936-39) frustrated these hopes and Miranda must exile at Mexico. 191 F. J. Dosil Mancilla et al. Faustino Miranda (1905-1964)...
Keywords: Faustino Miranda; History of Phycology; Station of marine biology of Pontevedra; Museo Nacional de Historia Natural of Madrid; Muséum National d'Histoire Na